Earth Science and Applications from Space: Urgent Needs and Opportunities to Serve the Nation - National Research Council (The National Academies Press, 2005)
The Earth is a dynamic planet whose changes and variations affect our communications, energy, health, food, housing, and transportation infrastructure. Understanding these changes requires a range of observations acquired from a variety of land-, sea-, air-, and space-based platforms. To assist NASA, NOAA, and the USGS develop these tools, the NRC was asked by these agencies to carry out a decadal strategy survey of Earth science and applications from space. In particular, the study is to develop the key scientific questions on which to focus Earth and environmental observations in the period 2005-2015, and a prioritized list of space programs, missions, and supporting activities to address these questions. This interim report outlines a key element of the study—the rationale for tying Earth observations to societal need—and identifies urgent near-term actions needed to achieve this goal. A final report, due in late 2006, will provide the list of recommended space missions, programs, and supporting.
Keywords: Space and Aeronautics

Automated Pavement Condition Survey Practices at Airports - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Pavement condition data are a critical component of pavement management programs. The accuracy and validity of pavement condition data are the basis for many activities conducted by airports and local agencies. ACRP Synthesis 124: Automated Pavement Condition Survey Practices at Airports, from TRB's Airport Cooperative Research Program, documents airport practices, challenges, and lessons learned in conducting automated pavement condition surveys, which are not always common practices at airports.
Keywords: Transportation and Infrastructure

A Plan for a Research Program on Aerosol Radiative Forcing and Climate Change - National Research Council (The National Academies Press, 1996)
This book recommends the initiation of an "integrated" research program to study the role of aerosols in the predicted global climate change. Current understanding suggest that, even now, aerosols, primarily from anthropogenic sources, may be reducing the rate of warming caused by greenhouse gas emissions. In addition to specific research recommendations, this book forcefully argues for two kinds of research program integration: integration of the individual laboratory, field, and theoretical research activities and an integrated management structure that involves all of the concerned federal agencies.
Keywords: Environment and Environmental Studies; Earth Sciences

Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design (The National Academies Press, 2023)
Since the inception of using sets of plans for construction purposes, a persistent challenge has been the miscommunication between designers and constructors, even when they were part of the same organization. NCHRP Web-Only Document 388: Framework for Implementing Constructability Throughout Project Development from NEPA to Final Design, from TRB's National Cooperative Highway Research Program, develops a decision-making framework that is scalable to all contract delivery methods and that complies with all environmental statutory requirements. Supplemental to the report are a technical memorandum, an adaptation guide for the framework toolkit, a full presentation, and an abridged presentation.
Keywords: Transportation and Infrastructure

Roadway Measurement System Evaluation - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2011)
TRB’s second Strategic Highway Research Program (SHRP 2) Report S2-S03-RW-1: Roadway Measurement System Evaluation documents the evaluation of automated, mobile data-collection services to provide data on roadway features and characteristics considered important for safety analysis, especially analysis of data from the SHRP 2 Naturalistic Driving Study.This report is only available in electronic format.
Keywords: Transportation and Infrastructure

Current Mesoscale Meteorological Research in the United States - National Research Council (The National Academies Press, 1981)
Keywords: Earth Sciences

Low-Altitude Wind Shear and Its Hazard to Aviation - National Research Council (The National Academies Press, 1983)
Keywords: Space and Aeronautics

Response to Extreme Weather Impacts on Transportation Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2014)
TRB’s National Cooperative Highway Research Program (NCHRP) Synthesis 454: Response to Extreme Weather Impacts on Transportation Systems examines eight recent cases of extreme weather in the United States from the perspectives of transportation operations, maintenance, design, construction, planning, communications, interagency coordination, and data and knowledge management.Appendices C-H are only available in the PDF version of the report.
Keywords: Transportation and Infrastructure

Assessment of NASA's Plans for Post-2002 Earth Observing Missions: Letter Report (The National Academies Press, 1999)
Keywords: Space and Aeronautics

Verifying Greenhouse Gas Emissions: Methods to Support International Climate Agreements - National Research Council (The National Academies Press, 2010)
The world's nations are moving toward agreements that will bind us together in an effort to limit future greenhouse gas emissions. With such agreements will come the need for all nations to make accurate estimates of greenhouse gas emissions and to monitor changes over time. In this context, the present book focuses on the greenhouse gases that result from human activities, have long lifetimes in the atmosphere and thus will change global climate for decades to millennia or more, and are currently included in international agreements. The book devotes considerably more space to CO2 than to the other gases because CO2 is the largest single contributor to global climate change and is thus the focus of many mitigation efforts. Only data in the public domain were considered because public access and transparency are necessary to build trust in a climate treaty. The book concludes that each country could estimate fossil-fuel CO2 emissions accurately enough to support monitoring of a climate treaty. However, current methods are not sufficiently accurate to check these self-reported estimates against independent data or to estimate other greenhouse gas emissions. Strategic investments would, within 5 years, improve reporting of emissions by countries and yield a useful capability for independent verification of greenhouse gas emissions reported by countries.
Keywords: Environment and Environmental Studies

Traffic Law Enforcement in Work Zones: Phase II Research - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2013)
TRB’s National Cooperative Highway Research Program (NCHRP) Web-Only Document 194: Traffic Law Enforcement in Work Zones: Phase II Research is contractor’s final report providing background information for the project that produced NCHRP Report 746 Traffic Enforcement Strategies for Work Zones.NCHRP Report 746 presents guidance for the safe and effective deployment of traffic enforcement strategies in work zones on high-speed highways.
Keywords: Transportation and Infrastructure

Uses of Mobile Information Technology Devices in the Field for Design, Construction, and Asset Management - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's National Cooperative Highway Research Program (NCHRP) Synthesis 491: Uses of Mobile Information Technology Devices in the Field for Design, Construction, and Asset Management documents the state-of-the-practice and state-of-the-art applications of state transportation agencies related to their use of mobile information technology (IT) devices. Specifically, the report reviews applications pertaining to the areas of design, construction, and asset management. Mobile IT devices such as laptop computers, mini-laptop computers, handheld multifunctional data collectors, tablets, and smartphones also play a role in bringing the transportation industry into digital platforms.
Keywords: Transportation and Infrastructure

Affordability of National Flood Insurance Program Premiums: Report 2 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
When Congress authorized the National Flood Insurance Program (NFIP) in 1968, it intended for the program to encourage community initiatives in flood risk management, charge insurance premiums consistent with actuarial pricing principles, and encourage the purchase of flood insurance by owners of flood prone properties, in part, by offering affordable premiums. The NFIP has been reauthorized many times since 1968, most recently with the Biggert-Waters Flood Insurance Reform Act of 2012 (BW 2012). In this most recent reauthorization, Congress placed a particular emphasis on setting flood insurance premiums following actuarial pricing principles, which was motivated by a desire to ensure future revenues were adequate to pay claims and administrative expenses. BW 2012 was designed to move the NFIP towards risk-based premiums for all flood insurance policies. The result was to be increased premiums for some policyholders that had been paying less than NFIP risk-based premiums and to possibly increase premiums for all policyholders. Recognition of this possibility and concern for the affordability of flood insurance is reflected in sections of the Homeowner Flood Insurance Affordability Act of 2014 (HFIAA 2014). These sections called on FEMA to propose a draft affordability framework for the NFIP after completing an analysis of the efforts of possible programs for offering "means-tested assistance" to policyholders for whom higher rates may not be affordable. BW 2012 and HFIAA 2014 mandated that FEMA conduct a study, in cooperation with the National Academies of Sciences, Engineering, and Medicine, which would compare the costs of a program of risk-based rates and means-tested assistance to the current system of subsidized flood insurance rates and federally funded disaster relief for people without coverage. Production of two reports was agreed upon to fulfill this mandate. This second report proposes alternative approaches for a national evaluation of affordability program policy options and includes lessons for the design of a national study from a proof-of-concept pilot study.
Keywords: Earth Sciences; Math, Chemistry, and Physics; Surveys and Statistics

Coastal Blue Carbon Approaches for Carbon Dioxide Removal and Reliable Sequestration: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Coastal environments provide many valuable ecosystem services. Their role as carbon sinks has been a topic of exploration to evaluate the potential for the restoration and management of coastal habitats as a viable carbon dioxide removal (CDR) approach. To explore the state of knowledge, technical research needs, costs, co-benefits, and societal and governance constraints of CDR in coastal ecosystems (often termed coastal blue carbon), the Committee on Developing a Research Agenda for Carbon Dioxide Removal and Sequestration convened its first workshop on July 26, 2017, in Woods Hole, Massachusetts. Invited speakers described their relevant work in order to provide the committee with an overview of the state of knowledge and research needs related to understanding carbon capacity and flux in coastal systems, the processes driving sustainability of coastal wetland carbon storage in the future, potential incentives for coastal blue carbon, and policy and governance challenges. The workshop was preceded by an introductory webinar on July 19, 2017, where invited speakers provided an overview of the ecosystems under consideration for coastal carbon removal and sequestration, as well as the costs and other considerations of restoring them. This publication summarizes the presentations from both the webinar and workshop.
Keywords: Earth Sciences; Environment and Environmental Studies

Improving AEDT Modeling for Aircraft Noise Reflection and Diffraction from Terrain and Manmade Structures - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Barriers, berms, buildings, and natural terrain may affect the propagation of aircraft noise by shielding or reflecting sound energy. If terrain and manmade structures obstruct the line‐of‐sight between the source and the receiver, then sound energy will be attenuated at the receiver. This attenuation increases with the terrain and structures’ size and proximity to either the source or the receiver. If gaps exist in the terrain or structures, then the potential benefits of acoustical shielding will be substantially reduced. Even when the line‐of‐sight is not obstructed, terrain can reflect the sound and create multiple pathways affecting the sound arriving at the receiver. The TRB Airport Cooperative Research Program's ACRP Web-Only Document 43: Improving AEDT Modeling for Aircraft Noise Reflection and Diffraction from Terrain and Manmade Structures seeks to develop and evaluate noise propagation methods that account for aircraft noise reflection and diffraction from terrain and manmade structures. It also recommends methods for inclusion into the AEDT (Aviation Environmental Design Tool) integrated noise modeling framework and provides updated AEDT user guidance on the influence terrain and man-made structures have on aircraft noise and the applications these new methods have for airport noise analyses.
Keywords: Transportation and Infrastructure

From Research to Reward: Social Science Studies the Most Hazardous Thing on the Road: You - National Academy of Sciences (The National Academies Press, 2016)
Keywords: Explore Science; Behavioral and Social Sciences

Transportation Asset Management: Summary of the 11th National Conference - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
TRB's Conference Proceedings on the Web 20: Transportation Asset Management: Summary of the 11th National Conference explores the discussions that took place on July 10–12, 2016, in Minneapolis, Minnesota. Conference presenters highlighted the advancements and improvements in transportation asset management programs at the state, regional, metropolitan, and local levels. Information on the innovative approaches used by transit and other modes was interwoven throughout the conference.
Keywords: Transportation and Infrastructure

Highway Hydraulic Engineering State of Practice - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The TRB National Cooperative Highway Research Program's NCHRP Synthesis 551: Highway Hydraulic Engineering State of Practice documents significant changes in highway hydraulic engineering practices implemented by state departments of transportation (DOTs) over the past decade.The synthesis focuses on eight subtopics of highway hydraulic engineering: roadway drainage; culvert aquatic organism passage; bridge scour computations and countermeasures; advanced hydraulic modeling; regulatory requirements; floodplain impacts and mitigation; coastal hydraulics; and alternative project delivery methods.
Keywords: Transportation and Infrastructure

Understanding Northern Latitude Vegetation Greening and Browning: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Vegetation change has been observed across Arctic and boreal regions. Studies have often documented large-scale greening trends, but they have also identified areas of browning or shifts between greening and browning over varying spatial extents and time periods. At the same time, though, there are large portions of these ecosystems that have not exhibited measurable trends in greening or browning. These findings have fueled many questions about the drivers of vegetation dynamics, how trends are measured, and potential implications of vegetation change at local to global scales. In December 2018, the National Academies of Sciences, Engineering, and Medicine, convened a workshop to discuss opportunities to improve understanding of greening and browning trends and drivers and the implications of these vegetation changes. The discussions included a close look at many of the methodological approaches used to evaluate greening and browning, as well as exploration of newer technologies that may help advance the science. This publication summarizes the presentations and discussions from the workshop.
Keywords: Earth Sciences

Practices for Integrated Flood Prediction and Response Systems - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
State departments of transportation (DOTs) and other state and local agencies have implemented integrated flood warning and response systems to mitigate the effects of floods. These systems are critical for staging personnel, deciding when to close roads, inspecting bridges, tracking floods throughout the state, and planning recovery.The TRB National Cooperative Highway Research Program's NCHRP Synthesis 573: Practices for Integrated Flood Prediction and Response Systems documents an overview of the state of the practice from agencies involved in finding new or innovative ways to improve flood management and response systems.Supplementary to the report is Appendix F, which includes sample documents of practices related to integrated flood prediction and response systems.
Keywords: Transportation and Infrastructure